Automatic Speed Surveillance and Vehicle Alerting System Using Internet of Things (IoT) - Gopal, Athira; D V, Haricharann; Harikoushik, A; V, Ambrish; VV, Vineeth (International Journal of Engineering and Technology, 2018)
With the number of vehicles increasing day by day monitor report equally increasing traffic violation of speed limits, the numbers of accidents that are caused because of the speeding have increased at an exponential rate. There are existing law enforcements that do condemn these activities, but the human nature tends to break those. With an autonomous and automated system to regulate the Speed control by taking the advantages of advancements in technologies available can help to bring down the violations of law and thereby bringing the law enforcements at a stricter fashion. Automatic Speed Surveillance and Vehicle Alerting System Using Internet of Things (IoT) makes it easy for the Law enforcers to make the riders to follow the rules in a more permissive way without affecting the flow of traffic and the ride. Connected with Radio Frequency Identification and Wi-Fi with a Controller, the system, when implemented can bring down the speeding problem, with the controls lying on human hand for more accurate and real-time traffic monitoring, thereby not affecting the flow of traffic too. An Indigenous surveillance and alerting system autonomously files the reports when the limits are crossed, making the process of penalizing more sophisticated, thereby exploiting the full potential of the system.Â Â